The Efficiency of Islamic Higher Education Curriculum in Indonesia : A Literature Review on Improving Intellectual Competence and Work Readiness Through Islamic Religious Education - Kardina Engelina Siregar; Ali Musri Semjan Putra (International Journal of Studies in International Education, 2024)
This study aims to analyze the efficiency of the curriculum of Islamic universities in Indonesia in ensuring the readiness of students to enter the workforce, by reviewing the role of Islamic religious education in improving intellectual competence. Through a literature study approach, this study identifies the challenges and opportunities faced by Islamic universities in integrating religious values ​​with the intellectual and professional needs of students. The main focus of this study is the effectiveness of the curriculum in balancing theoretical aspects of religion and practical skills needed in the workplace. This study found that the curriculum of Islamic universities in Indonesia has attempted to adopt an integrative approach that combines religious education with the development of soft skills and hard skills that are relevant to professional careers. However, there are still some weaknesses in the implementation, such as the lack of curriculum adjustment to the dynamics of the labor market, as well as the imbalance between religious education and practical skills. The results of this study indicate that Islamic religious education has an important role in shaping the character and professional ethics of students, which are the main capital in entering the workforce. Therefore, increasing the efficiency of the curriculum through collaboration between academics, industry practitioners, and policy makers is needed to ensure that students' intellectuality is in accordance with the demands of the workplace. This study contributes to the academic discussion on the reform of Islamic higher education curriculum and emphasizes the importance of Islamic religious education in producing graduates who are not only intellectually competent, but also have strong ethical values ​​to face professional challenges. The implication of this study is the need for a more flexible and adaptive curriculum strategy to improve the competitiveness of Islamic higher education graduates in the global job market.